2020
DOI: 10.1002/cjce.23698
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the denitrification efficiency over low‐rank activated coke by doping with transition metal oxides

Abstract: Low-rank activated coke (AC) is widely used for industrial flue gas purification due to its multipollutant cooperative removal capability. To enhance the denitrification capacity of AC for the selective catalytic reduction (SCR) of NO with NH 3 , several transition metal (Fe, Mn, Ce, V) oxides were uniformly loaded into AC by solvent impregnation. Compared to untreated AC, modified AC showed excellent denitrification efficiency above 90%. N 2 adsorptiondesorption and Raman spectroscopy techniques were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…At 125–135 °C, the NO X conversion increased about 4 times. At present, the widely used vanadium‐titanium catalyst has an active temperature window of 300–400 °C [30] . Therefore, it was considered that 125–135 °C was an appropriate temperature range for C‐ZFe.…”
Section: Methodsmentioning
confidence: 99%
“…At 125–135 °C, the NO X conversion increased about 4 times. At present, the widely used vanadium‐titanium catalyst has an active temperature window of 300–400 °C [30] . Therefore, it was considered that 125–135 °C was an appropriate temperature range for C‐ZFe.…”
Section: Methodsmentioning
confidence: 99%
“…The use of transition metals as the catalysts has been documented in some literature. 10,27,28 In addition, activated carbon as a structural carrier provided a suitable porous loading structure for iron. The denitrication process was mainly determined by the reducibility of activated carbon and the catalysis of elemental iron.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 99%
“…Studies have shown that it is superior to TiO 2 and SiO 2 in terms of resistance to ammonium sulfate, activated carbon, or coke as a carrier (Han et al 2018). Compared with the activated carbon, activated coke (AC) has the characteristics of low cost and high mechanical strength (Ye et al 2020). AC has a large specific surface area, abundant surface functional groups, and strong adsorption capacity, which had been successfully applied to SO 2 and Hg capture and NO x purification of flue gas in the steel industry (Liu and Liu 2013, Ye et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the activated carbon, activated coke (AC) has the characteristics of low cost and high mechanical strength (Ye et al 2020). AC has a large specific surface area, abundant surface functional groups, and strong adsorption capacity, which had been successfully applied to SO 2 and Hg capture and NO x purification of flue gas in the steel industry (Liu and Liu 2013, Ye et al 2020. Pure AC shows a low catalytic activity; thus, the method of introducing new active components (such as MnO x , CuO, or V 2 O 5 ) is used to enhance its denitration activity (Marban et al 2004;Boyano et al (Sun et al 2009;Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%